2018
DOI: 10.1002/ppp.1961
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale influences on thaw depth in a forested peat plateau landscape in the Northwest Territories, Canada: Vegetation trumps microtopography

Abstract: The influence of vegetation and microtopography on fine-scale variability of thaw depth is largely unknown but potentially important for improving modeling of ecosystem-permafrost interactions. To elucidate their influence, we measured tree density, shrub cover and cryptogam presence (lichen and bryophyte) on forested permafrost peat plateaus in the discontinuous permafrost zone in the southern Northwest Territories, Canada. Greater tree density was associated with shallower thaw depth (approximately one quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…These studies reveal large variations of Tnss at the landscape scale. In areas with fine‐grained sediments, summer thaw depth can be probed quickly at multiple locations 16–19 . Soil temperatures are seldom measured across active layer grids.…”
Section: Introductionmentioning
confidence: 99%
“…These studies reveal large variations of Tnss at the landscape scale. In areas with fine‐grained sediments, summer thaw depth can be probed quickly at multiple locations 16–19 . Soil temperatures are seldom measured across active layer grids.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that peat accumulation in the form of hummocks may promote the aggradation of permafrost due to the insulative properties of peat and the re‐establishment of black spruce; altering the energy dynamics of the landscape (Camill, 1999; Figure 9). Spatial variability in thaw depth was observed to be significantly impacted by hummock microforms and their associated vegetation resulting from thermal insulation facilitated by peat deposits (Higgins & Garon‐Labrecque, 2018). Carpino et al (2018) concluded that the return to a forest‐dominated landscape occurred in approximately 40 years (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Further monitoring of the hummock ice would be necessary to confirm if this ice persists interannually. The variability in thaw depth and potential promotion of ice formation due to the insulation afforded by hummocks (Higgins & Garon‐Labrecque, 2018) may have the potential to act as a positive feedback and further contribute to the vertical growth of hummock microtopography through expansion upon freezing (Figure 9); similar to the observed effects of ice formation on the development of mineral earth hummocks in the Canadian Arctic and Subarctic (Tarnocai & Zoltai, 1978) and peat plateaus at the southern boundary of the discontinuous permafrost zone (Zoltai, 1972). This potential positive feedback mechanism of ice formation on hummock growth requires further examination, particularly to assess its influence relative to the controls on NPP and organic matter accumulation known to drive hummock development in boreal peatlands (Belyea & Clymo, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The air-to-surface temperature dynamic and its relation to overall heat transfer involves a multivariate system. Many variables including vegetation (Smith, 1975), microtopography (Higgins and Garon-Labrecque, 2018), and snow cover (Zhang, 2005) affect the transfer of heat to and from the ground surface. Below ground, differences in soil conductivity play a role in the rate and extent of heat transferred and this is not only based on soil type but also moisture content (Gavril'ev, 1989).…”
Section: Background: Surface Temperature Modelsmentioning
confidence: 99%